2014
DOI: 10.3390/molecules19043926
|View full text |Cite
|
Sign up to set email alerts
|

Angelica sinensis Improves Exercise Performance and Protects against Physical Fatigue in Trained Mice

Abstract: Angelica sinensis (AS) is a well-known medicinal herb and food material with antioxidative and multifunctional pharmacological activities. However, we lack evidence of the effect of AS on exercise performance and physical fatigue. We aimed to evaluate the potential beneficial effect of AS on ergogenic and anti-fatigue functions after physiological challenge. Male ICR strain mice were randomly assigned to four groups (n = 10 per group) for treatment: (1) sedentary control and vehicle treatment (vehicle control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
17
1
1
Order By: Relevance
“…In addition, we did not identify an anti-inflammatory and anti-fatigue effect of DBT, as proposed in previous murine studies [ 25 , 26 ]. The levels of both TNF-α and IL-6 increased at Post-Ex and 24-h Rec.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, we did not identify an anti-inflammatory and anti-fatigue effect of DBT, as proposed in previous murine studies [ 25 , 26 ]. The levels of both TNF-α and IL-6 increased at Post-Ex and 24-h Rec.…”
Section: Discussionmentioning
confidence: 64%
“…An earlier study confirmed that DBT significantly increased iron absorption when being co-administrated with ferrous sulfate in iron-deficient anaemic rats [ 24 ]. In addition, previous studies published by our research group revealed that AM and AS have promising effects for improving exercise performance, ameliorating fatigue by reducing serum lactate and ammonia levels, as well as increasing muscle glycogen content and even promoting hypertrophy [ 25 , 26 , 27 , 28 ]. DBT may function in the normalisation of the levels of proinflammatory cytokines, tumour necrosis factor (TNF), and interleukin (IL), and in the elevation of endurance capacity in rats [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salvia reduces lipid peroxidation, lactate dehydrogenase, creatine kinase activities, enhanced antioxidant enzymes, and cholinesterase (ChE) activities in the skeletal muscle of endurance exercise rats; similar effects have been observed for other extracts, with some differences between each other, in which, additionally, antifatigue is measured also by forelimb grip strength and exhaustive swimming time as well as serum levels of lactate, ammonia, glucose, and creatine kinase after a 15 min swimming exercise. Specifically, the mechanisms of Acanthopanax (also called Eleutherococcus senticosus or Siberian ginseng) are the reduction of the level of triglycerides by increasing fat utilization, the delay of the accumulation of blood urea nitrogen (BUN), and the increase of the lactate dehydrogenase (LDH) to reduce the accumulation of lactic acid in muscle and then protect the muscle tissue [ 32 , 33 , 36 , 37 , 42 ]. Strange but active is Tao-Hong-Si-Wu-Tang that shows antifatigue activity in mice due to extended exhaustive swimming time, the increase of liver and muscle glycogen contents, and the decrease of the lactic acid (BLA) and urea nitrogen (BUN) plasmatic contents [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…처방구성은 당귀와 황기가 1:5의 비율로 구성되어 있으며, 이전 연구를 통해 항산화 효과 14,15) , 피부의 항염 효과 16) , 뼈형성과 신생혈관 형성에 대한 효과 17) 그리고 근육피로 18) 등에 효과가 있는 것으로 밝혀졌다. 또한 당귀보혈탕의 구성 단미(單味)인 당귀(當歸)에 대한 연구로는 항염증 19) 및 항산화 20) 효과, 근육피로에 대한 보호효과 21) 등이 보 고되었으며, 황기(黃芪)에 대한 연구로는 항산화 효과 22) , 허혈성 손상에서의 신생혈관생성 촉진 23) , 지질과산화 억 제 24) , 근육피로에 대한 개선효과 25) 및 근위축에 대한 방 There was no significant difference between Control and CGBHT groups.…”
Section: 당귀보혈탕(當歸補血湯)은 李東垣의 <內外傷辨惑論>에unclassified